Pesquisa e análise da aplicação de internet sem fio em ônibus de viagem - Souza, Rafael Moriggi de (2011)
Considering that modern life has led man to pursue the technology, speed and security needed to perform their daily tasks or even at your leisure. This confirms that for many users, mobility is essential because they must be connected at all times. Thus, the issue involved in this research takes the technology within the mobile Internet applied to buses, as a starting point for this study. The aim is to develop a survey from the companies collecting data, such as used equipment, mobile operators and plans. The study is a comparison between the companies already using this service, in order to offer a service that meets the needs of economy and comfort for its customers.